Symptoms and Risk Factors of Gastroesophageal Reflux Disease Among Medical Students in Oman - Al-rudaini, Mazin; Al Farsi, Hajer; Anwar, Zainab; Alwahshi, Aisha; Al Hinai, Raheel; Anwar, Sanam (International Journal of Innovative Research in Medical Science, 2024)
Background: There is a lack of studies related to the prevalence of gastroesophageal reflux disease (GERD) symptoms in Oman. The presence of the risk factors like consumption of caffeine-containing drinks, energy drinks, bad eating habits that contribute to the development of GERD were reported to be at a higher rate among medical students. This study was conducted to calculate the prevalence of GERD-related symptoms and the risk factors among medical students at the College of Medicine and Health Science, National University, Oman. Materials and methods: A questionnaire was circulated among the students of different study years which was based on the GERD Q-validated questionnaire. Additional questions were included regarding the presence of some of the risk factors of GERD. Results: Around 10.3% of the participants (43 out of 417) have satisfied the criteria of GERD Q with a statistically significant association (p>0.05) between high scoring GERD symptoms and body mass index (BMI), smoking, and the consumption of energy drinks. The most common symptoms reported were abdominal pain (59.7%), nausea (55.4%), burning sensation (47%), and regurgitation (45.6%). Conclusions: Due to the lifestyle of medical students and the high level of risk factors involved in the student's daily life; the possibility of developing GERD symptoms is high. Further confirmation of diagnosis by endoscopy will be needed.